2021
DOI: 10.1007/s00572-021-01041-6
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the relative importance of spatio-temporal parameters and host specificity in shaping arbuscular mycorrhizal fungus communities in a temperate forest

Abstract: Many woody and herbaceous plants in temperate forests cannot establish and survive in the absence of mycorrhizal associations. Most temperate forests are dominated by ectomycorrhizal woody plant species, which implies that the carrying capacity of the habitat for arbuscular mycorrhizal fungi (AMF) is relatively low and AMF could in some cases experience a limitation of propagules. Here we address how the AMF community composition varied in a small temperate forest site in Germany in relation to time, space, tw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 31 publications
3
7
0
Order By: Relevance
“…However, these processes could have been accelerated in the treatments in which the habitats were in the vicinity of one another and thus have given rise to our observations. Second, we believe that these results match well with a previous study we carried out at a much larger spatial scale which showed that in forest stands with high coverage of AMF-associating trees, the roots of the herbaceous understory were colonized more extensively with AMF than in stands maintaining a low-coverage of AMF-associating trees (Grünfeld et al 2019) even though they did not differ in AMF community composition (Grünfeld et al 2021). Both in Grünfeld et al (2019) and here, we observed that a relatively higher proximity to likely AMF hosts led to AMF more extensively colonizing plant hosts.…”
Section: High Connectance Habitats Of Medicago Lupulina Stimulate Amf...supporting
confidence: 88%
“…However, these processes could have been accelerated in the treatments in which the habitats were in the vicinity of one another and thus have given rise to our observations. Second, we believe that these results match well with a previous study we carried out at a much larger spatial scale which showed that in forest stands with high coverage of AMF-associating trees, the roots of the herbaceous understory were colonized more extensively with AMF than in stands maintaining a low-coverage of AMF-associating trees (Grünfeld et al 2019) even though they did not differ in AMF community composition (Grünfeld et al 2021). Both in Grünfeld et al (2019) and here, we observed that a relatively higher proximity to likely AMF hosts led to AMF more extensively colonizing plant hosts.…”
Section: High Connectance Habitats Of Medicago Lupulina Stimulate Amf...supporting
confidence: 88%
“…While Heklau et al ( 2021 ) described a significant relationship between AM colonization in the root system and OTU richness of Glomeromycota across different tree species, other studies attributed the variation in AM composition more to space than host identity or season. Analyzing the AM community composition of two understory forest plants (the deciduous shrub Euonymus europaea and the evergreen climber Hedera helix ) over different seasons, Grünfeld et al ( 2021 ) found that the physical distance between samples exerted a stronger influence on AM community composition than either sampling time or host specificity. In consequence, they encountered only a low seasonality in AM community composition.…”
Section: Discussionmentioning
confidence: 99%
“…In consequence, they encountered only a low seasonality in AM community composition. However, Grünfeld et al ( 2021 ) based these conclusions on molecular analyses without testing morphologically if arbuscules and vesicles as structures of active AM were present in the cortex cells of the host organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Richardson et al (2000) suggested that AM fungi likely play a small role in invasion outcomes due to the lack of host specificity in this symbiosis. However, AM fungal communities can differ between heterospecific neighbors (Bunn et al, 2014; Eom et al, 2000; Grünfeld et al, 2021; Reinhart & Anacker, 2014), suggesting some degree of host preference. Furthermore, plant species vary inter‐ and intraspecifically in their response to AM fungi (Koch et al, 2017; Reynolds et al, 2006; Walder et al, 2012).…”
Section: Introductionmentioning
confidence: 99%